Lower Hospitalization and Healthcare Costs With Sacubitril/Valsartan Versus Angiotensin‐Converting Enzyme Inhibitor or Angiotensin‐Receptor Blocker in a Retrospective Analysis of Patients With Heart Failure - Albert, Nancy M. (J Am Heart Assoc, 2019)
BACKGROUND: Outcomes data among patients with heart failure (HF) with reduced ejection fraction treated with sacubitril/valsartan (SAC/VAL) are largely limited to clinical trial results. We compared hospitalization and healthcare costs among real‐world patients with HF with reduced ejection fraction treated with SAC/VAL versus angiotensin‐converting enzyme inhibitor or angiotensin‐receptor blocker (ACEI/ARB). METHODS AND RESULTS: Using retrospective administrative claims data, stable patients with HF with reduced ejection fraction treated with SAC/VAL or ACEI/ARB from October 2015 to June 2016 were identified. Postindex hospitalization and healthcare costs were assessed in propensity‐matched cohorts using robust variance estimation. Time to first hospitalization was modeled using unadjusted Kaplan–Meier estimates and multivariable models. Postindex all‐cause healthcare costs were modeled using an adjusted multivariable model. Among 279 patients per matched cohort, postindex hospitalization risk was lower for SAC/VAL compared with ACEI/ARB using Kaplan–Meier estimation and unadjusted Cox models. For HF hospitalization, the hazard ratio (95% CI) was 0.56 (0.33–0.94; P=0.030). Adjusted results were similar to unadjusted. Mean (SD) monthly healthcare costs were lower for SAC/VAL versus ACEI/ARB for all categories except pharmacy, with hospital costs being particularly disparate between cohorts: for HF hospitalization, $248 ($1588) for SAC/VAL versus $1122 ($7290) for ACEI/ARB. The adjusted risk of incurring increased all‐cause postindex costs was lower for SAC/VAL versus ACEI/ARB (cost ratio [95% CI] 0.74 [0.59–0.94]; P=0.013). CONCLUSIONS: In clinical practice, patients with HF with reduced ejection fraction treated with SAC/VAL were less likely to be hospitalized than matched patients treated with ACEI/ARB. Despite higher pharmacy costs, SAC/VAL–treated patients incurred lower monthly medical and total healthcare costs.